Assembly time minimization of a particular placement machine - (:unkn) unknown (WORLD SCIENTIFIC AND ENGINEERING ACAD AND SOC, 2007)
A new algorithm for a component placement machine is proposed in this study. The new algorithm is compared with former approaches on synthetically generated benchmark instances. It outperforms the former approaches by 3.28% on printed circuit board with 100 components to be placed. We prove that this new approach works better in a typical PCB mounted in the industry, so can be applicable to the considered type of machine.
Keywords: printed circuit board assembly; traveling salesman problem; placement machine